2014
DOI: 10.3109/1354750x.2014.936911
|View full text |Cite
|
Sign up to set email alerts
|

Urinaryp-cresol is elevated in young French children with autism spectrum disorder: a replication study

Abstract: The aromatic compound p-cresol (4-methylphenol) has been found elevated in the urines of Italian autistic children up to 8 years of age. The present study aims at replicating these initial findings in an ethnically distinct sample and at extending them by measuring also the three components of urinary p-cresol, namely p-cresylsulfate, p-cresylglucuronate and free p-cresol. Total urinary p-cresol, p-cresylsulfate and p-cresylglucuronate were significantly elevated in 33 French autism spectrum disorder (ASD) cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 48 publications
(61 reference statements)
8
94
0
Order By: Relevance
“…At least some of the metabolic perturbations described here may reflect pathophysiologically meaningful abnormalities, possibly bearing functional consequences at the clinical level. Three strengths of the experimental design may have contributed to this positive outcome: (a) a focus on early infancy, by recruiting children within a relatively narrow age window precisely defined on the basis of previous urinary metabolic data [20, 21]; (b) the use of UHPLC-MS paired with HILIC, a very sensitive and reliable method ensuring maximum accuracy in the separation of small urinary solutes [26, 27]; (b) a pathway-centered approach, moving beyond the identification of single urinary ASD markers [1017], as beautifully exemplified by urinary metabolomic studies of rodent models of ASD [3537]. In particular, our recruitment strategy substantially differs from previous case-control study designs, minimizing age-dependent heterogeneity by setting data-driven age thresholds (i.e., 2–8 years old) [20, 21], and applying tight age and sex matching between cases and controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At least some of the metabolic perturbations described here may reflect pathophysiologically meaningful abnormalities, possibly bearing functional consequences at the clinical level. Three strengths of the experimental design may have contributed to this positive outcome: (a) a focus on early infancy, by recruiting children within a relatively narrow age window precisely defined on the basis of previous urinary metabolic data [20, 21]; (b) the use of UHPLC-MS paired with HILIC, a very sensitive and reliable method ensuring maximum accuracy in the separation of small urinary solutes [26, 27]; (b) a pathway-centered approach, moving beyond the identification of single urinary ASD markers [1017], as beautifully exemplified by urinary metabolomic studies of rodent models of ASD [3537]. In particular, our recruitment strategy substantially differs from previous case-control study designs, minimizing age-dependent heterogeneity by setting data-driven age thresholds (i.e., 2–8 years old) [20, 21], and applying tight age and sex matching between cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…These results point toward possible negative effects on CNS function exerted by microbiome-derived metabolites. At least three examples are available, albeit with different degrees of support: (a) urinary p -cresol amounts were found correlated with ASD severity [20] or with the intensity of stereotypic behaviors in young autistic children [21]; (b) i.c.v. injection of propionic acid, an enteric-derived short chain fatty acid, produces ASD-like behaviors in the rat [61]; (c) indoxyl sulfate is a known risk factor for cognitive impairment in chronic renal disease [62]: its influx across the blood-brain barrier using the organic anion transporter 3 significantly reduces the efflux of various neurotransmitter metabolites through the same transporter, leading to their accumulation [63].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have shown abnormal fecal metabolites, such as short chain fatty acids (SCFA) related to changes in microbiota[87]. Para-cresol (a phenolic compound) has been suggested to be a urinary marker for autism[88], especially in those with constipation and ASD[89]. In a mouse model of autism induced by maternal immune activation, autistic behaviors such as communication abnormalities, stereotypies, and anxiety behaviors were associated with abnormal serum metabolities produced by the microbiota, including 4-ethylphenyl sulfate (the major metabolite) and p-cresol (to a lesser extent)[57].…”
Section: Targeting the Gut Microbiome As A Potential Treatment For Chmentioning
confidence: 99%